2002
DOI: 10.1007/s00296-002-0201-3
|View full text |Cite
|
Sign up to set email alerts
|

Poststreptococcal reactive arthritis in children: is it really a different entity from rheumatic fever?

Abstract: Poststreptococcal reactive arthritis (PSRA) is an acute, nonsuppurative arthritis following documented streptococcal infections. Although most authors accepted it as a different entity, the differences from acute rheumatic fever (ARF) are not clear. To document and compare the clinical and laboratory characteristics of PSRA and ARF, 24 patients with PSRA and 20 with ARF were enrolled in the study. The latency period from upper respiratory tract infection was shorter in patients with PSRA ( P<0.01). However, 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 6 publications
3
10
2
1
Order By: Relevance
“…In ARF, carditis occurs in 50% of children compared with 33% of adults (12,13,(28)(29)(30). In 3 previous studies, investigators performed echocardiographic screening for valvular heart disease in 12, 24, and 40 children, respectively (29)(30)(31). Of all 76 of those patients, valvular disease was detected in 6 (7.9%).…”
Section: Discussionmentioning
confidence: 99%
“…In ARF, carditis occurs in 50% of children compared with 33% of adults (12,13,(28)(29)(30). In 3 previous studies, investigators performed echocardiographic screening for valvular heart disease in 12, 24, and 40 children, respectively (29)(30)(31). Of all 76 of those patients, valvular disease was detected in 6 (7.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Before using this information in a clinical setting, it may be valuable for other large prospective studies to determine the risk of valvular heart disease in adults with poststreptococcal ReA, in order to ascertain whether the findings of our study can be replicated. We read with interest the recent article by Carter et al, which described an increased frequency of Chlamydia-positive synovial tissue samples, as determined by polymerase chain reaction (PCR), in patients with chronic undifferentiated spondylarthritis (uSpA) (1). This observation is a major step forward in elucidating the etiology of uSpA but is most likely also relevant for the whole spectrum of SpA.…”
Section: To the Editormentioning
confidence: 80%
“…Our goal was to determine the increased risk of carditis (previously unknown) in adult patients with poststreptococcal ReA. Studies on ARF have shown that the risk of carditis in adults is lower than in children (33% versus 50%) (1)(2)(3). In children with poststreptococcal ReA, the risk of carditis is ϳ8% (1-3), and in adults, as mentioned above, the risk had yet to be determined.…”
Section: To the Editormentioning
confidence: 99%
“…Many authors consider post-strep arthritis a distinct disease from RF. [155][156][157][158][159] Care must be taken that a silent carditis does not go undetected [160][161][162][163] and more than one echocardiogram is sometimes wise. It should be added that RF and post-streptococcal arthritis often lead to different perspectives from different subspecialties; rheumatologists, infectious disease experts, and cardiologists may have different views of RF due to their clinical experience and the type of post-streptococcal disease that presents to their clinics; therefore, conflict in opinions regarding diagnosis and treatment are inevitable.…”
Section: Rheumatic Fever and Post-strep Arthritismentioning
confidence: 99%